A Conceptual Model for Individual Coping with Value Conflicts. Issue 3 (22nd April 2021) - Jaspers, Sylke
Abstract: Conflicting values that are sometimes impossible to resolve are one of the costs of public governance for public values and public outcomes. To unravel one of the mechanisms enhancing or obstructing public values or public outcomes in public governance, this article presents the individual coping with value conflicts model. The model focuses on individually experienced value conflicts regarding public values realization (i.e., the principles of governance) and public value creation (i.e., public outcomes) necessitating coping strategies. The article discusses various aspects of the theoretical model. The various coping strategies and their likely results are connected to public values realization and public value creation. However, first, the article identifies the origins of the need to rely on coping strategies, such as value pluralism and plural expectations of individuals. Next, the paper hypothesizes that individual coping strategies are driven by the psychological traits of individuals and influenced by interactions. The article further explains that the individual's role in adopting coping strategies manifests in specific situations or contexts. The paper concludes with implications for public value(s) theories, makes suggestions for applications of the model, and sets out avenues for empirical research to test and advance the model.